A moving target: Multiples occurrences of left lung torsion secondary to adenocarcinoma and pleural effusion. Issue 6 (8th December 2022) - Skead, Charlenn; Carle-Talbot, Katia; Ochoa-Gomez, Diana; Amjadi, Kayvan; Gupta, Ashish
Abstract: A patient with left upper lobe adenocarcinoma was found to have asymptomatic left lung torsion in the context of a pleural effusion. With drainage of the pleural effusion the mass returned to its original position. Multiple torsion events were documented and found to only occur in presence of a pleural effusion. This case suggests a new possible indication for indwelling pleural catheter (IPC) placement.